THE IMPACT OF WORK ENVIRONMENT AND INCENTIVES ON EMPLOYEE’S JOB PERFORMANCE THROUGH MEDIATING ROLE OF JOB SATISFACTION DURING THE COVID-19 PANDEMIC - Yenita , Yenita; Tania, Johanna (Graduate Program of Universitas Tarumanagara, 2023)
In service companies, employees play an important role in helping the company to achieve its business goals, thus, it is important for companies to recruit competent employees. Then, to retain the high-performance employee, companies have to create a supportive and comfortable work environment, as well as providing incentives as bonuses to increase employee job satisfaction. This study is to analyze the impact of work environment and incentives on employee’s job performance during Covid-19 pandemic through job satisfaction as a mediating role. This study uses quantitative descriptive method by distributing questionnaires to 190 employees in an express shipping services company. PLS-based Structure Equation Modeling (SEM) technique with 95% confidence level has been used for analysis and generating results. Incentives found to have a positive and significant effect on employee’s job performance. Work environment and incentives are found to have a positive and significant effect on job satisfaction. Job satisfaction is found to have a positive but not significant effect on mediating the relation between work environment and incentives on employee’s job performance. Therefore, working environment and incentive appear to be effective ways to improve job satisfaction, and incentives can improve employee’s job performance.